Perirenal fat metastasis of prostate cancer - Teppei Wakita; Kazuaki Yamanaka; Akihiro Yoshimura; Shota Fukae; Takahiro Yoshida; Hidefumi Kishikawa (Urology Case Reports, 2021)
A 72-year-old male underwent an abdominal CT scan, which revealed a 17-mm nodular incidentaloma in fat tissue in the left perirenal space. Retroperitoneoscopic surgery was performed to remove the tumor and histopathological results revealed a PSA-positive adenocarcinoma, which was diagnosed as a metastatic lesion associated with prostate cancer. PSA was high at 30.083 ng/ml and MRI findings showed extracapsular extension of prostate cancer in the left peripheral zone of the prostate gland. Biopsy results with a Gleason score of 4 + 4 confirmed the diagnosis of prostate cancer. The case was diagnosed as prostate cancer metastasis in perirenal fat tissue.